ANALYSIS OF THE IMPACT OF FOOT-AND-MOUTH DISEASE ON PRODUCTION MANAGEMENT AND BUSINESS FEASIBILITY OF SAPI SONOK IN SUMENEP REGENCY - Wulandari, Islami; Sri Hidanah; Soeharsono (Universitas Airlangga, 2025)
This study aims to determine the impact of foot and mouth disease (FMD) on production management consisting of maintenance management, cage management, health management, feed management and business analysis of sonok cattle in Potre Koning Sonok Cattle Association in Lenteng Sub-district, Sumenep District. This study used 21 respondents consisting of 20 association members and one paramedic. The primary and secondary data were obtained from the distribution of questionnaires and interviews. Questionnaire data are divided into three groups: before FMD, during FMD, and post-FMD, which were then analyzed using the Manova test and the Duncan test. The results showed significant differences in housing management, health management, feed management, and business analysis (p<0.05). Housing management showed no significant difference in the time before, during and after FMD, while business analysis during FMD suffered losses due to decreased productivity of sonok cattle. Health management is the most influential management during FMD. Farmers ignore the profitability of raising sonok cattle because sonok cattle are a hobby for farmers.